Prefusion RSV F Immunization Elicits Th2-Mediated Lung Pathology in Mice When Formulated With a Th2 (but Not a Th1/Th2-Balanced) Adjuvant Despite Complete Viral Protection - Eichinger, Katherine M.; Kosanovich, Jessica L.; Gidwani, Sonal V.; Zomback, Aaron; Lipp, Madeline A.; Perkins, Timothy N.; Oury, Tim D.; Petrovsky, Nikolai; Marshall, Christopher P.; Yondola, Mark A.; Empey, Kerry M. (Frontiers in Immunology, 2020)
Respiratory syncytial virus (RSV) remains the most common cause of lower respiratory tract infections in children worldwide. Development of a vaccine has been hindered by the risk of developing enhanced respiratory disease (ERD) upon natural exposure to the virus. Generation of higher quality neutralizing antibodies with stabilized pre-fusion F protein antigens has been proposed as a strategy to prevent ERD. We sought to test whether there was evidence of ERD in naïve BALB/c mice immunized with an unadjuvanted, stabilized pre-fusion F protein, and challenged with RSV line 19. We further sought to determine the extent to which formulation with a Th2-biased (alum) or a more Th1/Th2-balanced (Advax-SM) adjuvant influenced cellular responses and lung pathology. When exposed to RSV, mice immunized with pre-fusion F protein alone (PreF) exhibited increased airway eosinophilia and mucus accumulation. This was further exacerbated by formulation of PreF with Alum (aluminum hydroxide). Conversely, formulation of PreF with a Th1/Th2-balanced adjuvant, Advax-SM, not only suppressed RSV viral replication, but also inhibited airway eosinophilia and mucus accumulation. This was associated with lower numbers of lung innate lymphocytes (ILC2s) and CD4+ T cells producing IL-5+ or IL-13+ and increased IFN+ CD4+ and CD8+ T cells, in addition to RSV F-specific CD8+ T cells. These data suggest that in the absence of preimmunity, stabilized PreF antigens may still be associated with aberrant Th2 responses that induce lung pathology in response to RSV infection, and can be prevented by formulation with more Th1/Th2-balanced adjuvants that enhance CD4+ and CD8+ IFN+ T cell responses. This may support the use of stabilized PreF antigens with Th1/Th2-balanced adjuvants like, Advax-SM, as safer alternatives to alum in RSV vaccine candidates.